Exploring hurricane wind speed along US Atlantic coast in warming climate and effects on predictions of structural damage and intervention costs. (1st September 2016) - Cui, Wei; Caracoglia, Luca
Highlights: Residuals of linear regression in hurricane track simulation are discussed. A relation between temperature and hurricane annual frequency is proposed. Time-dependent temperature field is employed to predict hurricane intensity. Lifetime damage cost due to hurricane is calculated under climate change. Non-stationary structural failure probability is used to predict damage cost. Abstract: This paper proposes a methodology for the rational assessment of lifetime costs on tall buildings due to hurricane-induced damage along the US Atlantic coastline accounting for plausible future warming climate scenarios. The hurricane simulation is based on Vickery's empirical model. Initially, regression errors in Vickery's model are discussed; some adjustments are proposed to enable hurricane simulation in future climates. After verification of the hurricane model's ability to simulate the results of the United States historical hurricane database, simulation of hurricane activity in future climates is examined. The warming climate scenarios are reproduced from the results of the community earth system model, maintained by the National Center for Atmospheric Research (NCAR). Three different future climate scenarios, RCP2.6, RCP4.5 and RCP8.5, are considered. The influence of warming climate on two quantities, relevant to wind engineering, is examined: hurricane frequency and hurricane intensity. It is found that, in a warming climate environment, the hurricane frequency and hurricane intensity may vary depending on the RCP scenario. Therefore, the probability distribution of the wind speed in hurricane-prone areas of the United States, both coastal and interior areas, will also be influenced by the RCPs. The numerical methodology for computing wind speed probability distribution in a future warming climate, influenced by the various RCP scenarios, is subsequently coupled with an existing approach for structural performance analysis against wind hazards to predict the indirect effect of future warming climate on the structural intervention costs (i.e. repair costs), induced by the damaging winds. A 180-m tall benchmark building, located in Miami (Florida, USA), is used as one example of application in conjunction with a series of structural fragility curves, derived from a recent study for the same structure. The evaluation of lifetime intervention costs is later expanded to demonstrate the ability of the proposed methodology to predict hurricane wind damage, if the location of the structure is moved to several other cities along the Atlantic coast of the United States.